If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 7) + -8 = x + 9 Reorder the terms: 2(7 + x) + -8 = x + 9 (7 * 2 + x * 2) + -8 = x + 9 (14 + 2x) + -8 = x + 9 Reorder the terms: 14 + -8 + 2x = x + 9 Combine like terms: 14 + -8 = 6 6 + 2x = x + 9 Reorder the terms: 6 + 2x = 9 + x Solving 6 + 2x = 9 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 6 + 2x + -1x = 9 + x + -1x Combine like terms: 2x + -1x = 1x 6 + 1x = 9 + x + -1x Combine like terms: x + -1x = 0 6 + 1x = 9 + 0 6 + 1x = 9 Add '-6' to each side of the equation. 6 + -6 + 1x = 9 + -6 Combine like terms: 6 + -6 = 0 0 + 1x = 9 + -6 1x = 9 + -6 Combine like terms: 9 + -6 = 3 1x = 3 Divide each side by '1'. x = 3 Simplifying x = 3
| 8=3+y | | 6+55x=33x+14 | | 18=(x+y) | | 9=t/12 | | (4x^2-1)-(18x^2-9x)=0 | | cos(4x-pi/2) | | 12psquared-8=0 | | 5x+35=1+6x | | 7x+45=5x-85 | | .06x+.1x=1764.4 | | 196/14 | | 7/8x-7/8=4 | | 343/196 | | 5.18x+25.9=51.8 | | 6.94x+81=48.1636+9x | | 94=2d+80 | | 6b=15+2a | | -ln(3x+1)-5=ln(x+4) | | 6.6(x-2)=-0.4x+35.8 | | 3.95+.05x=2+.10x | | -2.35=-19.95+1.10w | | 6x^2+5=15 | | 17=-7v+3(v-5) | | p/16=-11 | | 3x+6=-48-3x | | (x-2)(2x+3)=-6 | | 6=6x+6 | | 0.08x+0.5(x+200)=140.6 | | 4y^2+4y+7=0 | | x-12(8-x)=x+3(4-x)-x | | 4(x+2)=2(3x-2) | | 6=6x-6 |